Heme oxygenase-1 prevents liver fibrosis in rats by regulating the expression of PPARγ and NF-κB - Yang, Hui (Baishideng Publishing Group Co., Limited, 2012)
AIM: To investigate the effects of heme oxygenase (HO)-1 on liver fibrosis and the expression of peroxisome proliferator-activated receptor gamma (PPARγ) and nuclear factor-kappa B (NF-κB) in rats. METHODS: Sixty Wistar rats were used to construct liver fibrosis models and were randomly divided into 5 groups: group A (normal, untreated), group B (model for 4 wk, untreated), group C (model for 6 wk, untreated), group D [model for 6 wk, treated with zinc protoporphyrin IX (ZnPP-IX) from week 4 to week 6], group E (model for 6 wk, treated with hemin from week 4 to week 6). Next, liver injury was assessed by measuring serum alanine aminotransferase (ALT), aspartate aminotransferase (AST) and albumin levels. The degree of hepatic fibrosis was evaluated by measuring serum hyaluronate acid (HA), type IV collagen (IV-C) and by histological examination. Hydroxyproline (Hyp) content in the liver homogenate was determined. The expression levels of alpha-smooth muscle actin (α-SMA) in liver tissue were measured by real-time quantitative polymerase chain reaction (RT-PCR). The expression levels of PPARγ and NF-κB were determined by RT-PCR and Western blotting. RESULTS: The expression of HO-1 increased with the development of fibrosis. Induction of HO-1 by hemin significantly attenuated the severity of liver injury and the levels of liver fibrosis as compared with inhibition of HO-1 by ZnPP-IX. The concentrations of serum ALT, AST, HA and IV-C in group E decreased compared with group C and group D (P < 0.01). Amount of Hyp and α-SMA in the liver tissues in group E decreased compared with group C (0.62 ± 0.14 vs 0.84 ± 0.07, 1.42 ± 0.17 vs 1.84 ± 0.17, respectively, P < 0.01) and group D (0.62 ± 0.14 vs 1.11 ± 0.16, 1.42 ± 0.17 vs 2.56 ± 0.37, respectively, P < 0.01). The expression of PPARγ at levels of transcription and translation decreased with the development of fibrosis especially in group D; and it increased in group E compared with groups C and D (0.88 ± 0.15 vs 0.56 ± 0.19, 0.88 ± 0.15 vs 0.41 ± 0.11, respectively, P < 0.01). The expression of NF-κB increased with the development of fibrosis especially in group D; and it decreased in group E compared with groups C and D (1.43 ± 0.31 vs 1.89 ± 0.29, 1.43 ± 0.31 vs 2.53 ± 0.54, respectively, P < 0.01). CONCLUSION: Our data demonstrate a potential mechanism that HO-1 can prevent liver fibrosis by enhancing the expression of PPARγ and decreasing the expression of NF-κB in liver tissues.